Pengaruh Kualitas Pelayanan Prima Terhadap Kepuasan Pasien Rawat Inap di RSIA Kartini Padalarang - Rizal Ardiansyah; fransiska Agustina (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine the effect of excellent service on patient satisfaction at RSIA Kartini Padalarang. The method used is a Quantitative research method with the number of samples in this study is 110 respondents. The data collection techniques used are literature research and distributing questionnaires. The data analysis method used is multiple linear regression, multiple correlation and coefficient of determination to explain the relationship and influence between independent and dependent variables. The results showed that there was an effect of excellent service on patient satisfaction by 51.9% at RSIA Kartini Padalarang.